Coupled Coincidence Point and Coupled Fixed Point Theorems via Generalized Meir-Keeler Type Contractions - Hassen Aydi; Erdal Karapınar; İnci M. Erhan (Abstract and Applied Analysis)
We prove coupled coincidence point and coupled fixed point results of 𝐹∶𝑋×𝑋→𝑋 and 𝑔∶𝑋→𝑋 involving Meir-Keeler type contractions on the class of partially ordered metric spaces. Our results generalize some recent results in the literature. Also, we give some illustrative examples and application.